Sistem Pakar Diagnosis Penyakit Tanaman Cengkeh Menggunakan Metode Naive Bayes (Studi kasus Kecamatan Wonosalam, Jombang) - Andrianto Setiawan; Nurul Hidayat; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Clove plants are classified into plantation crops or industries that are widely grown in Wonosalam. But not all clove plantations belong to the local people, but the owners are residents from outside the region. This causes the plant is less well groomed cloves and eventually attacked by disease. One method to diagnose clove plant disease can be done with Naive Bayes. Clove plant disease diagnosis expert system using Naive Bayes method can make it easier to detect diseases that attack the cloves based on the symptoms that arise. The Naive Bayes method is implemented on an expert system inference engine in order to make inferences based on existing knowledge on the knowledge base. Results obtained after a system accuracy test of 93% indicating that the method of Naive Bayes is suitable for clove plant disease cases.